2021
DOI: 10.4251/wjgo.v13.i8.772
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitor-mediated colitis in gastrointestinal malignancies and inflammatory bowel disease

Abstract: Immune checkpoint inhibitors (ICI) have markedly changed the landscape of cancer therapy. By re-invigorating the immune system against tumors, ICI provide novel therapeutic options for a broad variety of malignancies, including many gastrointestinal (GI) cancers. However, these therapies can also induce autoimmune-like side effects in healthy tissue across the body. One of the most common of these side effects is ICI-mediated colitis and diarrhea (IMC). Here, we review the incidence and risk of IMC in ICI ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 122 publications
(179 reference statements)
0
7
0
Order By: Relevance
“…This higher incidence of diarrhea was also noted when a PD-1/PDL1 and a TKI were used in combination [49 && ]. Other predictors of ICPi colitis include the type of malignancy, race, sex, age, lack of vitamin D supplementation, and recent pneumococcal pneumonia vaccine [53].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This higher incidence of diarrhea was also noted when a PD-1/PDL1 and a TKI were used in combination [49 && ]. Other predictors of ICPi colitis include the type of malignancy, race, sex, age, lack of vitamin D supplementation, and recent pneumococcal pneumonia vaccine [53].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Other predictors of ICPi colitis include the type of malignancy, race, sex, age, lack of vitamin D supplementation, and recent pneumococcal pneumonia vaccine [53].…”
Section: Introductionmentioning
confidence: 99%
“…This involves uncontrolled T-cell and B-cell proliferation in multiple organs, leading to a widespread multi-organ inflammatory condition, typically involving dermatitis, nephritis, hepatitis, and colitis. ICI also interacts with interleukin-17 production [31]. Mice studies showed that the administration of PDL-1 antibodies can dampen IL-17 concentration in the colon, which may explain why PDL-1 therapies have fewer colonic irAEs compared to CTLA-4 [31][32][33].…”
Section: Pathophysiology Of Immune-related Git Eventsmentioning
confidence: 99%
“…ICI also interacts with interleukin-17 production [31]. Mice studies showed that the administration of PDL-1 antibodies can dampen IL-17 concentration in the colon, which may explain why PDL-1 therapies have fewer colonic irAEs compared to CTLA-4 [31][32][33]. Changes in the population of resident CD8+ T-cells in the colon were also speculated to enhance inflammatory response [34].…”
Section: Pathophysiology Of Immune-related Git Eventsmentioning
confidence: 99%
“…There is even a consideration that a certain level of diarrhea has a favorable outcome and is a proxy way to see therapy effectiveness. In one study of patients with metastatic melanoma, those who develop irAEs including colitis were associated with improved OS and progression-free survival (PFS) [24 ▪ ].…”
Section: Treatmentmentioning
confidence: 99%